Pemetaan Bibliometrik Penerapan ISO 31000 : 2018 sebagai Standar Manajemen Risiko : Analisis Visual Berbasis VOSviewer - Indri Iswardhani (Jurnal bintang manajemen, 2025)
This study aims to map the development of literature on the implementation of ISO 31000:2018 as a risk management standard through bibliometric analysis. Using VOSviewer software, this study analyzed 500 scientific articles sourced from Google Scholar. Citation metric analysis results show significant research productivity and impact, with a total of 4,514 citations, an h-index of 34, and a collaboration pattern with an average of 2.40 authors per article. Keyword network mapping identified five main thematic clusters: (1) Risk Management Operational Processes and Stages; (2) Framework and Standard Implementation; (3) Specific Analysis Methods (FMEA); (4) Enterprise Risk Management and Case Study Approaches; and (5) Technology Application. The research findings reveal that this field of study has reached a good level of maturity, with the main focus still on the technical aspects of standard implementation, but has expanded towards integration with digital transformation and enterprise-level risk management approaches. The results of this study can serve as a guide for academics and practitioners in identifying research trends and future risk management development.